The effect of pre-treatment levels of tooth wear and the applied increase in the vertical dimension of occlusion (VDO) on the survival of direct resin composite restorations. (August 2021) - Mehta, Shamir B.; Bronkhorst, Ewald M.; Lima, Verônica P.; Crins, Luuk; Bronkhorst, Hilde; Opdam, Niek J.M.; Huysmans, Marie-Charlotte D.N.J.M.; Loomans, Bas A.C.
Abstract: Objectives: To investigate the effects of the level of pre-treatment tooth wear and increasing the VDO on the performance of direct resin composite restorations for the rehabilitation of pathological tooth wear. Methods: Full-mouth (pre-treatment) grading was performed on digital greyscale scan records for 34 participants (35.3 ± 8.4 years) with signs of moderate-to-severe generalised tooth wear, using the Tooth Wear Evaluation System and the Basic Erosive Wear Examination. Each participant received full-mouth direct resin composite restorations, with increased VDO. The post-treatment increase in the VDO was determined. Recalls were planned after 1 month, and after 1, 3, and 5 years. Three 'levels' of restoration failure were described. The effects of the variables on the frequencies of restoration failure were calculated with a multivariable Cox regression, ( p < 0.05). Results: 1269 restorations were placed with a mean observation period of 62.4 months. Increasing the VDO by 1 mm significantly reduced the risks of all levels of anterior restoration failure (HR ≤ 0.62, p ≤ 0.025). A higher anterior BEWE surface score was associated with increased risks of Level 2- & 3- failures, (HR ≥ 1.29, p ≤ 0.019). Premolar restorations showed lower risks of Level 2- & 3- failure, compared to the molar restorations, (HR ≤ 0.5, p ≤ 0.005). Conclusion: Levels of pre-treatment wear and the applied change in the VDO significantly affected failure risk. Clinical relevance: Direct resin composite restorations for the rehabilitation of wear should be made as voluminous as possible, respecting the presenting biological, functional, and esthetic constraints.